Counter Narrative Strategy of Terrorism Mitigation National Agency in Preventing Terrorism through Online Media - Wirantoko, Dodik; Wahyudi, Bambang (Journal of Strategic and Global Studies, 2018)
The spread of terrorist radicalism could not be stopped by government and various related agencies’ policy with their decisive actions such as blocking the sites, blogs, accounts, or even arresting the site or account owner. The explicit approach through legal enforcement is very important, however it needs integrative effort through collaboration of soft approach such as counter-narrative efforts which applied by BNPT in order to get the core of problem. This research attempts to analyze counternarrative effort held by BNPT through counter-narrative theory of Sarah Zeiger (2016) in preventing the spread of terrorism through online media. This research used qualitative descriptive method such as literature review and in-depth interview with numbers of figures from BNPT and the experts. The results of study found that monitoring through online media needs to be done at any time as an early detection process in order to obtain accurate information of potential terrorism spreading which is mostly representing ideology and religion. The counter-narrative strategy is carried out through two approaches, first through online on BNPT’s website and second through offline by conducting direct meeting with audience in form of socialization, workshop and training. Furthermore, all components of society needs to be involved especially the audience as media community. The number of counter-narrative strategy for audience in responding the potential threat of radical terrorism through BNPT’s site is relatively small compared with number of internet users. However, together with the strengthening of national insight, diversity and love for Indonesia through counternarrative could contribute more for National Resilience.